Quality and Seed Growth of Melon (Curcuma melo L.) in Different Drying Period and Storage Period - Azka, Millati; Anwar, Syaiful; Kusmiyati, Florentina (Journal of Tropical Crop Science and Technology, 2021)
The objective of this research was to study the effect of drying and storage period on seed quality and seed growth of melon (Curcuma melo L.). This research was assigned in Nested Design with first factor was storage period (P1 = 0 week, P2 = 2 weeks, P3 = 4 weeks, dan P4 = 6 weeks) and drying period (L1 = 0 hours, L2 = 12 hours, dan L3 = 24 hours). Parameter observed were seed moisture content, seed germination, seed maximum growth potency, length of plants, and number of leaves. The result showed that drying period showed significant affect on seed moisture content. Storage period showed significant affect on seed germination, seed maximum growth potency, and length of plants. Both storage period and drying period didn’t show significant affect on the number of melon leaves.